On non-linear and non-ideal interactions in two vibrating problems - Felix, J.L. Palácios [UNESP]; Brasil, R. M L R F; Balthazar, José Manoel [UNESP]; Krasnopolskaya, T. S.; Shevets, A. Y. (ASME International, 2008)
In practical situations, the dynamics of the forcing function on a vibrating system cannot be considered as given a priori, and it must be taken as a consequence of the dynamics of the whole system. In other words, the forcing source has limited power, as that provided by a DC motor for an example, and thus its own dynamics is influenced by that of the vibrating system being forced. This increases the number of degrees of freedom of the problem, and it is called a non-ideal problem. In this work, we considerer two non-ideal problems analyzed by using numerical simulations. The existence of the Sommerfeld effect was verified, that is, the effect of getting stuck at resonance (energy imparted to the DC motor being used to excite large amplitude motions of the supporting structure). We considered two kinds of non-ideal problem: one related to the transverse vibrations of a shaft carrying two disks and another to a piezoceramic bar transducer powered by a vacuum tube generated by a non-ideal source Copyright © 2007 by ASME.
Keywords: At resonance; Energy imparted; Forcing functions; international conferences; International designs; Large-amplitude motions; Multi-body system (MBS); Non-linear; Non-linear dynamics; Number of degrees of freedom; Numerical simulations; Piezoceramic (PZT); Sommerfeld effect; Supporting structures; Technical conferences; Transverse vibrations; Vibrating systems; Architectural design; Computer control; Computer networks; Computer simulation; Computers; Control systems; DC generator motors; DC motors; Dynamical systems; Electric motors; Engineering; Information systems; Mechanics; Motors; Nonlinear programming; Photoacoustic effect; Technology; Vibrations (mechanical); Dynamics